STUDI BERAT BADAN ANAK BALITA SETELAH DILAKUKAN PIJAT TUINAÂ DI POSYANDU DUSUN KEDUNG KLINTER DESA CANGGU KECAMATAN JETIS KABUPATEN MOJOKERTO - YUSWO YANI, LASIYATI; PRASETYO, ERWIN (JURNAL KEPERAWATAN SEHAT, 2016)
Childrens health needs attention, especially children who do not like to eat so as to require direction to increase appetite. Factors that cause the occurrence of malnutrition is the lack of nutrient intake, because the child is difficult to eat. Tuina massage is an alternative in increasing appetite in small. This study aims to determine the weight of children under five after done tuina massage. Type of research used is one group pre test-post test design. Population in this research is all balita at posyandu Dusun Kedung Klinter Canggu Village Jetis Subdistrict Mojokerto Regency as many as 29 children under five. The sample is some toddlers in Posyandu as many as 16 respondents This research uses purposive sampling, experiment in the form of 8 steps tuina massage and weighing tool balita. After the data collected, then performed data processing through the stages of Editing, Coding. The result of the discussion about the influence of tuina massage in children aged 3-5 years can be concluded that after doing tuina massage body weight of toddlers known that almost all respondents weighing badanya after given tuina massage in fixed category as many as 15 respondents (93,75%). Tuina massage can stimulate the nerves in the digestive system so that the absorption of optimal nutria that can increase the childs weight.Keywords: Weight Gain, Tuina Massage